Improving Mathematics Achievement and Students’ Activity at Primary Level using STAD Learning Model - Nurulhikmah, Arisyta; Kristin, Firosalia (Jurnal Pendidikan Progresif, 2019)
Improving mathematics achievement and students’ activity at primary level using STAD model. Objectives: This study aims to improve the activities and learning outcomes of primary students using STAD model. Methods: The research subject were 42 of fourth grade students at SDN Salatiga 01 on 2017/2018 academic year. The data obtained in this study include qualitative and quantitative data. The research instruments used included the lesson plan, test instruments, and non-test instruments. Findings: The percentage of learning activities of students in the first phase was77% and increased to 81.5% in the second phase. The percentage of classical learning completeness in the first and second phase were 67% and 76%, respectively. Conclusions: STAD model is effective to improve students’ activity and mathematics achievement.Keywords: STAD model, mathematics achievement, learning activity, primary school students. DOI: http://dx.doi.org/10.23960/jpp.v9.i1.201913